Penggunaan Media Bervariasi dalam Meningkatkan Minat Belajar Siswa - Jeane Tulung; Orient Christianty (Peneliti.net, 2022)
The purpose of this study was to determine the use of various methods of inhibiting factors and how to overcome obstacles in the use of varied methods in increasing student interest in learning at SMP Negeri 4 Tombariri. The method used is a qualitative research conducted at SMP Negeri 4 Tombariri. Data were collected through observation, interviews, and documentation that had gone through the data analysis stage. Based on the results of research and discussion, it can be concluded that there is still a lack of use of variation methods by teachers so that students are not interested in learning or students' interest in learning is reduced. The factors that hinder the use of the variation method in the learning process are the teacher's lack of mastery of various methods or methods of variation in learning and the lack of learning media in supporting the application of the variation method. Efforts made by teachers to increase student interest in learning by using variation methods in the pandemic era are by directing students to be able to use smartphones in the learning process as a supporting medium to achieve learning goals.